Ten new species of Cephennula Jałoszyński (Coleoptera, Staphylinidae, Scydmaeninae) from Malaysia - Jałoszyński, Paweł (Zootaxa, 2011)
Ten new species of the ant-like stone beetle genus Cephennula Jałoszyński (Scydmaeninae, Cephenniini) are described, all occurring in Malaysia: C. densepunctata sp. n. (Sabah), C. gemina sp. n.(Sabah), C. minutissima sp. n. (Sarawak), C. penrissenana sp. n. (Sarawak), C. poringana sp. n. (Sabah), C. sibugana sp. n. (Sabah), C. titiwangsana sp. n. (Pahang), C. medioglabra sp. n. (Pahang), C. micropunctata sp. n. (Pahang) and C. gombakiana sp. n. (Selangor). Habitus and aedeagus of each species are illustrated. Two informal species groups―Cephennula minuta group and Cephennula multicarinata group―are proposed to divide Cephennula into possibly natural lineages; monophyly of these groups remains to be tested.